Climate control of litter decomposition and nutrient release in tropical and sub-tropical forest biomes of Northeast India - Ngangbam Somen Singh; Francis Q Brearley; Shri Kant Tripathi (Environmental Advances)
Litter decomposition is fundamental to nutrient cycling in forest ecosystems across the globe and is affected by abiotic and biotic factors. Thus, patterns of litter decomposition and nutrient release vary among different terrestrial ecosystems depending on climatic conditions. We followed the decomposition of litter from four species as well as a mixed litter in contrasting sub-tropical (STF) and tropical (TF) forests of North-east India to assess the factors influencing decomposition between them. Mass loss and concentrations of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), manganese (Mn) and sulfur (S), as well as acid-unhydrolyzable residue (AUR) (‘lignin’) were followed over a one-year period. We found clearly different decomposition patterns in the two forest types. In the TF, decomposition followed the single exponential function indicating a complete disappearance of litter material within a year. In contrast, in the STF, the mass loss pattern followed an asymptotic function with a limit value indicating a stable fraction. The AUR decomposition rate was about twice as fast in the TF as compared to the STF. Litter decomposition and nutrient release were faster in the TF compared to the STF, and hence carbon and nutrients were accrued in the soil organic matter in the latter but not in the former due to contrasting environmental conditions. It is concluded that the mechanism for complete decomposition in TF as compared to STF is strongly influenced by the climate rather than any intrinsic factors.